Invitro And Insilico Study With GC-MS Profiling for Assessment of Antioxidant and Anticancer Activity of The Methanolic Extracts of Annona Squamosa L. Leaves - Biswas, Palash Chandra; Jakhmola, Vikash; Samanta, Arnab (Journal of Neonatal Surgery, 2025)
Annona Squamosa L, (sugar apple or custard apple) belongs to tiny plant- family Annonaceae is a tropical plant species, known for its sweet edible fruits and is a reach source of secondary metabolites, (Quercetin, kaempferol, Catechin, Epicatechin, Epigallocatechin gallate etc) .In this study we have performed the phytochemical screening, Total phenolic, flavonoid and terpenoid contents Antioxidant activity, anti-cancer and cytotoxic activity of methanolic leaf extracts from Annona Squamosa L.. The free radical scavenging activities were investigated through H2O2 assay. To evaluate the anticancer and cytotoxic activity MTT Assay was performed. In this study we have done GC-MS and LC-MS to find out the name and % abundance of flavonoid of interest and from the result we have find out the presences of following flavonoid compounds those are most useful to treat different type of cancer and Endometriosis for its angiogenesis and antifibrotic properties. (1) Kaempferol, (2) Epigallocatechin (EGC), (3) Quercetin and (4) Epigallocatechin – 3 – Gallate (EGCG). Molecular docking method was employed to find out the anticancer activity of the phytoconstituents. Ethnopharmacological study (the study of interrelation between humans and plants including plants used as food, medicine and in other human applications) revels the information of different plant part and their useful preparation method. At the same time in vitro and in vivo studies and clinical tests will provide the proof of evidence that will support the ethnopharmacological report.